Academic Success in the Oral Presentation Course and Overall Self-Confidence - Ferri Hidayad; Dewi Lestari; Adieli Laoli; Samsul Anam; Despita (Asian Journal of Applied Education (AJAE), 2023)
The investigation of the relationship between overall self-confidence and academic success in the oral presentation course was a special focus of the study. 53 female undergraduate English majors from PGRI University of Palembang participated in the study. The General Self-Confidence Questionnaire (GSCQ) and final evaluation scores for the Oral Presentation course were used to gather data. Data analysis was done using SPSS. The findings showed a significant, positive association between general self-confidence and academic success. High GSCQ scorers also performed well on the oral achievement test. In order to improve their students' achievement in oral performance, language instructors were advised to increase the development of their students' self-confidence.